Pola Protein Sekret Kelenjar Parotoid Tiga Spesies Kodok dan Sekret Kelenjar Kulit Katak Kongkang Racun (Odorrana hosii Boulenger,1891) Melalui SDS-PAGE - Oktavina, Mega Ayu (Prosiding KPSDA, 2015)
Toads (Phrynoidis aspera, Ingerophrynus biporcatus, Duttaphrynus melanostictus) and poisonous rock-frog (Odorrana hosii) are members of the class Amphibian from different Families. Previously, those three species toads were in the same genus called Bufo, but now they are clustered in a different genus based on the molecular systematic. Proteins secrete from the parotoid and skin glands are one of self-defense mechanisms against to predators. The aims of this study were to determine and compare the protein patterns in secretes from toad parotoid gland and skin gland of poisonous rock-frog. The specimens were obtained from sampling at several different locations according to their habitats. Secrete collections were done by stressing both physically and chemically. Secrete was extracted by the addition of acid and sonication. The secrete protein concentration was measured by the Bradford test, whereas protein patterns were analyzed by SDS-PAGE. The protein concentrations of secrete from toadâs parotoid gland are higher (Phrynoidis aspera 3.50 Âµg/ml; Duttaphrynus melanostictus 6.7 Âµg/ml Ingerophrynus biporcatus 1.32 Âµg/ml) than in skin gland secretion of poisonous rock- frog (1.07 Âµg/ml). There are 6 protein bands in parotoid gland secretion of Phrynoidis aspera, 5 protein bands in parotoid gland secretion Ingerophrynus biporcatus and 7 protein bands in secrete of Duttaphrynus melanostictus parotoid glands with molecular weight ranges 12.09-172.51 kDa. However, those proteins are different size of molecular weights for each species.Â Furthermore, two protein bands (with different densities) are founded in skin gland secretion of poisonous rock-frog with molecular weight of 66.17 kDa and 78.73 kDa. The differences of genes, habitats and predators may influence the differences of protein patterns in secrete from toadâs paratoid gland and frogâs skin glands. Those protein patterns could be useful for further studies, especially on Bufo systematic, also for exploring the potential of protein secrete as antibacterial or antifungal.